Pengaruh Budaya Organisasi dan Kompetensi Digital terhadap Kinerja Pegawai pada Dinas SDA, Cipta Karya dan Tata Ruang Provinsi Sulawesi Selatan - Hasniwati Hasniwati; M Yusuf Alfian Rendra Anggoro KR; Andi Risfan Rizaldi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of Organizational Culture and Digital Competence on Employee Performance at the Department of Water Resources, Human Settlements, and Spatial Planning of South Sulawesi Province. The phenomenon of digital transformation demands in government organizations still causes challenges in technology adaptation, differences in employee digital competencies, and the need to strengthen organizational culture to be able to support improved employee performance. The study used a quantitative approach with a survey method through the distribution of questionnaires to employees. The population in this study amounted to 105 employees, with a sample of 53 respondents determined using a purposive sampling technique. The research instrument includes three variables, namely Organizational Culture, Digital Competence, and Employee Performance measured based on predetermined operational indicators. The results of the study indicate that organizational culture and digital competency have a positive and significant influence on employee performance. This study concludes that strengthening an adaptive organizational culture and improving employee digital competency are important factors in supporting employee performance, especially in facing the demands of digital transformation in the government sector.